Formation of core-shell nanostructure through wrapping of cuprous oxide nanowires by hydrogen titanate nanotubes. (July 2022) - Patra, Shyamapada; Das, Pritam; Rajbhar, Manoj K.; Facsko, Stefan; Möller, Wolfhard; Chatterjee, Shyamal
Abstract: Recent developments of heterojunction-based devices through bottom-up approach such as sensors, light-emitters, energy generation and storage have emerged with great interest due to their wide range of operation and application related flexibilities. This work demonstrates how as-grown hydrogen titanate nanotubes (HTNT) bend and wrap on pristine curpous oxide nanowires (CONW) when mixed together. The unique architecture of wrapping followed by junction formation enhances the active surface area and reduces the contact resistance between the adjacent CONW and HTNT. Such a film upon further ion beam irradiation produces a large-scale network of hetero- and homo-junctions. This newly formed thin film surface upon irradiation shows strong water repelling properties and higher electrical conductivity. The wrapping mechanism, bond formation and the change of conductivity are explained using first principles calculations. The ion beam modifications and large-scale joining are predicted by state-of-the-art TRI3DYN simulation, which is based on binary collision approximation and simulated in a Monte Carlo approach. The observed wrapping and heterojunction are expected to provide excellent mechanical strength and flexibility, which are suitable for fabrication of flexible electronic devices. Highlights: Self-wrapping and junction formation of two different one-dimensional nanostructured metal oxides (Cu2 O and H2 Ti3 O7 ). Ion beam mixing and joining of two dissimilar ceramic nanowire and nanotube respectively. Formation of core-shell p-n junction by self-wrapping and ion beam mixing. The study provides an outlook regarding bonding involved, exchange of atoms and density of states due to wrapping and ion beam mixing.